Les ruines résonnent encore de leurs pas. La circulation dans les monuments grecs (VIIe s. - 31 a.C.) - Dromain, Marietta (PrimaLun@, 2021)
Research on Greek monuments has only rarely, or only superficially, intersected with research in the socio-historical field. However, the multidisciplinary orientation of current research allows us to consider architecture from a new angle, by placing Man at the heart of the subject. In fact, recreating paths and gestures that have disappeared today requires a cross-referencing of sources, particularly textual, epigraphic, archaeological and iconographic. It is in this perspective that the International Study Day on the Circulation of Greek Monuments was held on 3rd and 4th November 2016. The aim of this event, which is taken up in this publication, was twofold: to fill a gap and to raise questions that could lead, in the long run, to new studies.